2021
DOI: 10.1088/1757-899x/1098/3/032099
|View full text |Cite
|
Sign up to set email alerts
|

Virtual laboratory of science on symbiotic material for primary school students

Abstract: Practical activities in learning science often experience constraint in terms of tools, materials, places and time. These constraints hinder the acquisition of facts, concepts and theories of science. The purpose of this study was to develop a learning media in the form of virtual laboratory to teach Science (symbiotic). In developing virtual laboratory media, the steps that should be followed include defining problem, designing system, programming, testing, operational and maintenance and evaluation. This med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
0
4
0
1
Order By: Relevance
“…The findings from the teachers revealed that conducting practical experiments in the VL platform is much more affordable and that resource-constrained rural schools can make use of the VL as an alternative to the real lab. This is supported by Lestari andSupahar (2020), andKumala et al, (2021). The following are the comments from the teachers in this study.…”
Section: Affordability Of Teaching Using the Vlmentioning
confidence: 60%
See 1 more Smart Citation
“…The findings from the teachers revealed that conducting practical experiments in the VL platform is much more affordable and that resource-constrained rural schools can make use of the VL as an alternative to the real lab. This is supported by Lestari andSupahar (2020), andKumala et al, (2021). The following are the comments from the teachers in this study.…”
Section: Affordability Of Teaching Using the Vlmentioning
confidence: 60%
“…Recently, a robust symbiotic relationship between science education and ICT in education has developed in which the two are joined by an 'umbilical cord' of mutual benefit. This relationship has drastically transformed the laboratory science education landscape (Kumala et al, 2021;Eliyawati et al, 2021), and a new form of laboratory, Virtual Lab (VL), has emerged. VL is a simulated version of a traditional laboratory in which the learner is provided with instruments that are virtual representations of real objects used in conventional laboratories (Lestari & Supahar, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Khususnya dalam pembelajaran IPA, praktek langsung merupakan hal wajib yang harus dilaksankana ketika melaksanakan pembelajaran pada materi materi tertentu. Namun kendala di lapangan, praktek langsung sering kali juga sulit diwujudkan karena bahan yang mahal (Tüysüz, 2010;Yusuf & Subaer, 2013), berbahaya (Suyatna, 2009), membutuhkan waktu (Asih et al, 2016;Cengiz Tüysüz, 2010;Yuniarti et al, 2012), dan keterbatasan tempat yang dimiliki (Kumala et al, 2021;Kumala, 2017).…”
Section: Pendahuluanunclassified
“…In an effort to accommodate practical activities that are not possible to carry out in a real laboratory, one of the efforts that can be made is by elaborating and developing a virtual lab (Kumala et al 2021;Arifin et al 2020;Revenchuk et al 2020;Erlina, 2018;Yeni, 2015). The elaboration and development are both in the context of learning media (Muhajarah & Shulton, 2020) and in the context of development as laboratory media (Zhang et al 2016;Luo & Chhabda, 2015;Liem et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Virtual labs are actually able to stimulate the improvement of students' scientific literacy skills (Alneyadi, 2019;Ismail et al 2016). In addition, the use of virtual labs is able to stimulate the improvement of students' chemical scientific behavior (Koehler, 2021).…”
Section: Introductionmentioning
confidence: 99%